(untitled) (Research, Society and Development, 2022)
The food packaging process is of immense importance when it comes to preserving fresh or processed foods. Most of these materials are made from synthetic plastics and their disposal represents an environmental problem. This study aimed to prepare and characterize films composed of biopolymers, sodium alginate (SA) and carboxymethylcellulose (CMC), with the addition of arabic gum and fennel essential oil. Contact angle analysis shows that the films are hydrophilic. The surface of the films presented a firm, dense and cohesive structure, but with some roughness. In the micrographs of the film samples containing fennel essential oil, crystal-like structures can be observed on the polymer matrix of CMC and AS. The humidity of the films was, in general, low (average of 14%). The lowest percentages of moisture presented were for films with essential oil. Films are biodegradable, this process occurs because natural macromolecules such as proteins, polysaccharides, cellulose and gum are generally degradable in biological systems by hydrolysis followed by oxidation. Therefore, the formation of edible packaging containing polysaccharides and fennel essential oil emulsion was satisfactory.